2004
DOI: 10.4161/cc.3.10.1195
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Redundant Functions of Histone Deacetylases in Regulation of Cell Cycle and Apoptosis

Abstract: Inappropriate control of expression of genetic information is the cause of many forms of cancer. Aberrant transcriptional repression by recruitment of histone deacetylases (HDACs) is a key step in pathogenesis of myeloid leukemia. We recently reported that development of colonic cancer involves alterations in the transcriptional repression machinery by increased expression of HDAC2 upon loss of the APC tumor suppressor. Increased expression of HDAC2 is essential for prevention of apoptosis of HT-29 colonic can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 14 publications
5
26
0
Order By: Relevance
“…Our results show that valproate causes time-dependent increment of p21 WAF1 expression in ESS-1 cells. There are data suggesting that, at least in colonic cancer cells, HDAC2 down-regulation does not influence p21 WAF1 expression (35). Our data imply that these processes are cell and tissue specific and depend on methods and/or substances used for HDAC inhibition.…”
Section: Discussionmentioning
confidence: 75%
“…Our results show that valproate causes time-dependent increment of p21 WAF1 expression in ESS-1 cells. There are data suggesting that, at least in colonic cancer cells, HDAC2 down-regulation does not influence p21 WAF1 expression (35). Our data imply that these processes are cell and tissue specific and depend on methods and/or substances used for HDAC inhibition.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies found that HDAC2 played an important role in tumor cell proliferation, cell cycle control and other cellular processes (28,29). A high level of HDAC expression promotes tumoral cell proliferation, regulates the cell cycle, increases tumor angiogenesis, and upregulates the expression of various oncogenes (27).…”
Section: Discussionmentioning
confidence: 99%
“…The selective disruption of HDAC1 was found to result in embryonic lethality despite its elevating HDAC2 and HDAC3 expressions (26). HDAC2 seems to preferentially act to prevent apoptosis, and not act in cell cycle control similar to the specific importance of HDAC1 in cell cycle regulation (27). HDAC8 associates with the smooth muscle actin cytoskeleton and may regulate the contraction of smooth muscle cells (28).…”
Section: Discussionmentioning
confidence: 99%